The association between market-determined and accounting-determined risk measures in the South African context - J. L.R. Retief; J. F. Affleck-Graves; W. D. Hamman (South African Journal of Business Management, 1986)
A key problem in estimating the cost of capital for an unlisted company has been the determination of its beta coefficient. Market prices for such companies are not available, therefore the traditional regression methods for estimation are not possible. Thus, it is necessary for a proxy beta to be determined. In this article an attempt is made to develop such a proxy beta by using eight accounting variables. These accounting variables are shown to be significantly correlated to the market beta for individual companies. In addition, regression analyses are performed to develop an estimation model which will allow the individual company to obtain a proxy beta from its accounting variables. Satisfactory regression equations are developed for both the single share case and the portfolio case. The article is concluded with the presentation of a four-step procedure which will permit managers of unlisted companies to obtain a proxy for their beta and hence to estimate their overall cost of capital. In addition, it is shown that the procedure presented is consistent with the findings of modern portfolio theory.
Keywords: 650